Optothermoplasmonic Nanolithography for On‐Demand Patterning of 2D Materials. (12th August 2018) - Lin, Linhan; Li, Jingang; Li, Wei; Yogeesh, Maruthi N.; Shi, Jianjian; Peng, Xiaolei; Liu, Yaoran; Rajeeva, Bharath Bangalore; Becker, Michael F.; Liu, Yuanyue; Akinwande, Deji; Zheng, Yuebing
Abstract: Since the first discovery of graphene, 2D materials are drawing tremendous attention due to their atomic thickness and superior properties. Fabrication of high‐quality micro‐/nanopatterns of 2D materials is essential for their applications in both nanoelectronics and nanophotonics. In this work, an all‐optical lithographic technique, optothermoplasmonic nanolithography (OTNL), is developed to achieve high‐throughput, versatile, and maskless patterning of different atomic layers. Low‐power (≈5 mW µm −2 ) and high‐resolution patterning of both graphene and MoS2 monolayers is demonstrated through exploiting thermal oxidation and sublimation at the highly localized thermoplasmonic hotspots. Density functional theory simulations reveal that Au nanoparticles reduce the formation energy (≈0.6 eV) of C monovacancies through bonding between undercoordinated C and Au, leading to a significant Au‐catalyzed graphene oxidation and a reduction of the required laser operation power. Programmable patterning of 2D materials into complex and large‐scale nanostructures is further demonstrated. With its low‐power, high‐resolution, and versatile patterning capability, OTNL offers the possibility to scale up the fabrication of nanostructured 2D materials for many applications in photonic and electronic devices. Abstract : Optothermoplasmonic nanolithography (OTNL) is developed for low‐power, high‐throughput, and on‐demand patterning of different 2D materials. The variable high‐resolution patterns on 2D monolayers are fabricated through exploiting thermal oxidation and sublimation at the localized thermoplasmonic hotspots. OTNL offers the scalable fabrication of nanostructured 2D materials for various applications.